An ontology for software engineering teaching modules. (10th September 2007) - Ellis, Heidi J.C.; Hislop, Gregory W.
The World Wide Web is increasingly being used to allow both educators and learners to more easily locate desired information, as well as to support integration of related materials from different sources. This paper reports on an ontology constructed for the Network Community for Software Engineering Education (SWENET) and represents a teaching perspective on software engineering material. The addition of semantic mark up to teaching modules based on the SWENET ontology would allow instructors and learners to access material in the manner that best fits their educational needs, increase reuse of teaching materials and support integration with existing learning objects.